Film and layered body
By optimizing the cured resin layer's surface roughness and element ratios through controlled plasma processing, the film and laminated body achieve enhanced adhesion and visibility by minimizing light scattering and unevenness.
Patent Information
- Application Number
- JP2023113720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-07-11
Smart Images

Figure 2025014129000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a film and a laminate, and more particularly to a film and a laminate including the film. [Background technology]
[0002] In order to reduce the weight and improve the functionality of electronic products, composite materials that combine organic and inorganic materials have been developed. Known examples of composite materials include laminated films that include an organic substrate film and an inorganic layer on the substrate film.
[0003] As such a laminate film, for example, a hard coat film having a film substrate and a hard coat layer in this order, and an antireflection film having an inorganic oxide primer layer and an antireflection layer in this order have been proposed (see, for example, Patent Document 1).
[0004] In Patent Document 1, before forming a primer layer on the hard coat layer, the hard coat layer is subjected to a plasma treatment. By such a treatment, dirt and moisture on the surface of the hard coat film (hard coat layer) can be removed, and the adhesion between the hard coat film and the antireflection layer can be improved. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2022-65437 Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, the base film is required to have even better adhesion. In order to improve the adhesion, it has been considered to dispose a cured resin layer containing inorganic particles on the surface of the base film and improve the adhesion between the base film and the inorganic layer by the anchor effect caused by the irregularities due to the inorganic particles.
[0007] However, since the irregularities caused by the inorganic particles are non-uniform, the light is diffused or scattered on the surface of the cured resin layer, resulting in a problem of reduced visibility. In addition to the external scattering on the surface, the visibility is also reduced due to internal scattering inside the cured resin layer caused by the difference between the refractive index of the cured resin layer and the refractive index of the inorganic particles.
[0008] The present invention provides a film having excellent adhesion and visibility, and a laminate including the film. [Means for solving the problem]
[0009] The present invention [1] is a film comprising a base layer and a cured resin layer, in that order, toward one side in a thickness direction, wherein the arithmetic mean roughness Sa of one surface in the thickness direction of the cured resin layer is 0.80 nm or more and 4.50 nm or less, the minimum autocorrelation length Sal of one surface in the thickness direction of the cured resin layer is 40 nm or less, and the developed area Sdr of one surface in the thickness direction of the cured resin layer is 1.0% or more and 30% or less.
[0010] The present invention [2] is characterized in that the carbon element ratio C 90 , oxygen element ratio O 90 , carbon element ratio C 15 and oxygen element ratio O 15 The present invention includes the film described in [1] above, which satisfies the following formula (1). O 15 / C 15 >O 90 / C 90 (1) Test: (1) Using X-ray photoelectron spectroscopy, the photoelectron take-off angle was adjusted to 90° with respect to one surface in the thickness direction of the cured resin layer, and the carbon element ratio C 90 and oxygen element ratio O90 Measure. (2) Using X-ray photoelectron spectroscopy, the photoelectron take-off angle was adjusted to 15° with respect to one surface in the thickness direction of the cured resin layer, and the carbon element ratio C 15 and oxygen element ratio O 15 Measure.
[0011] The present invention [3] includes a laminate comprising the film according to the above [1] or [2] and an inorganic layer in that order toward one side in the thickness direction.
[0012] The present invention [4] includes the laminate according to the above [3], in which the inorganic layer is an anti-reflection layer, and the anti-reflection layer includes a plurality of layers having different refractive indices along the thickness direction.
[0013] The present invention [5] includes the laminate according to the above [3], in which the inorganic layer is a conductive layer. Effect of the Invention
[0014] In the film of the present invention, the arithmetic mean roughness Sa and the developed area Sdr of one surface in the thickness direction of the cured resin layer are within a predetermined range, thereby improving the adhesion.
[0015] Furthermore, the minimum autocorrelation length Sal of one surface in the thickness direction of the cured resin layer is equal to or less than a predetermined value, which improves visibility.
[0016] The laminate of the present invention includes the film of the present invention and an inorganic layer in this order toward one side in the thickness direction, and therefore has excellent adhesion between the film and the inorganic layer, and also has excellent visibility. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 shows one embodiment of the film of the present invention. [Diagram 2] FIG. 2 is a perspective view showing the positional relationship between the low inductance antenna and the intermediate laminate. [Diagram 3]FIG. 3 is a cross-sectional view showing the positional relationship between the low inductance antenna and the intermediate laminate. [Figure 4] FIG. 4 shows one embodiment of the laminate of the present invention. [Diagram 5] FIG. 5 shows an embodiment of the stack in which the inorganic layer is an anti-reflective layer. [Figure 6] FIG. 6 shows the surface shape of one surface in the thickness direction of the hard coat layer of the film of Example 1. [Figure 7] FIG. 7 shows the surface shape of one surface in the thickness direction of the hard coat layer of the film of Example 2. [Figure 8] FIG. 8 shows the surface shape of one surface in the thickness direction of the hard coat layer of the film of Comparative Example 1. [Figure 9] FIG. 9 shows the surface shape of one surface in the thickness direction of the hard coat layer in the film of Comparative Example 2. [Figure 10] FIG. 10 shows the surface shape of one surface in the thickness direction of the hard coat layer in the film of Comparative Example 3. [Figure 11] FIG. 11 shows the surface shape of one surface in the thickness direction of the hard coat layer in the film of Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] One embodiment of the film of the present invention will be described with reference to FIG.
[0019] In FIG. 1, the up-down direction of the paper is the up-down direction (thickness direction). The upper side of the paper is the top side (one side in the thickness direction). The lower side of the paper is the bottom side (the other side in the thickness direction). The left-right direction and the depth direction of the paper are surface directions perpendicular to the up-down direction. Specifically, they follow the directional arrows in each figure.
[0020] The film 1 has a film shape (including a sheet shape) with a predetermined thickness. The film 1 extends in a plane direction perpendicular to the thickness direction. The film 1 has a flat upper surface and a flat lower surface. The film 1 is preferably flexible.
[0021] The film 1 preferably has transparency. Specifically, the total light transmittance (JIS K 7375-2008) of the film 1 is, for example, 80% or more, or preferably 85% or more.
[0022] The thickness of the film 1 is, for example, 10 μm or more, preferably 20 μm or more, and more preferably 35 μm or more, and from the viewpoint of handleability in the roll-to-roll method described later, for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 60 μm or less.
[0023] The thickness of the film 1 can be measured using a dial gauge (manufactured by PEACOCK, "DG-205").
[0024] The film 1 includes a base material layer 3 and a cured resin layer 4 in this order toward one side in the thickness direction. Specifically, the film 1 includes the base material layer 3 and the cured resin layer 4 disposed directly on the upper surface (one surface in the thickness direction) of the base material layer 3. The film 1 preferably includes the base material layer 3 and the cured resin layer 4.
[0025] <Base material layer> The base layer 3 is a base material for ensuring the mechanical strength of the film 1.
[0026] The base layer 3 has a film shape and is preferably flexible.
[0027] The substrate layer 3 may be, for example, a polymer film.
[0028] Examples of materials for the polymer film include polyester resin, (meth)acrylic resin, olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, and polystyrene resin. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of (meth)acrylic resin include polymethyl methacrylate. Examples of olefin resin include polyethylene, polypropylene, and cycloolefin polymer. Examples of cellulose resin include triacetyl cellulose.
[0029] As the material of the polymer film, a cellulose resin is preferable, and a triacetyl cellulose is more preferable.
[0030] The thickness of the base layer 3 is, for example, 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more from the viewpoint of ensuring mechanical strength, and, for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, and further preferably 50 μm or less from the viewpoint of handleability in the roll-to-roll method described later. A carrier film may be attached to the back surface of the film 1 in order to ensure transportability and handleability of the base layer 3 in the roll-to-roll method process.
[0031] The thickness of the base layer 3 can be measured using a dial gauge (manufactured by PEACOCK, "DG-205").
[0032] The base layer 3 preferably has transparency. Specifically, the total light transmittance (JIS K 7375-2008) of the base layer 3 is, for example, 80% or more, or preferably 85% or more.
[0033] <Cured resin layer> The cured resin layer 4 has a film shape. The cured resin layer 4 is disposed on the entire upper surface of the base layer 3 so as to be in contact with the upper surface of the base layer 3. The cured resin layer 4 is the uppermost layer of the film 1.
[0034] Examples of the cured resin layer 4 include a hard coat layer, an easy adhesion layer, and an anti-blocking (AB) layer. A preferred example of the cured resin layer 4 is a hard coat layer. The hard coat layer is an abrasion protection layer that makes the film 1 less susceptible to abrasions.
[0035] The hard coat layer is a cured product of a hard coat composition containing a curable resin.
[0036] Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin. Examples of the curable resin include preferably acrylic urethane resin. That is, the hard coat layer preferably includes acrylic urethane resin.
[0037] The curable resins can be used alone or in combination of two or more kinds.
[0038] Examples of the curable resin include ultraviolet curable resin and thermosetting resin. The curable resin is preferably an ultraviolet curable resin. If the curable resin is an ultraviolet curable resin, the curable resin can be cured without heating, and therefore the production efficiency of the film 1 can be improved.
[0039] In the hard coat composition, the content of the curable resin is, for example, 80 mass % or more, preferably 90 mass % or more, and for example, 99 mass % or less, preferably 95 mass % or less.
[0040] The hard coat composition optionally contains other curable resins (e.g., polyester resins, amide resins, silicone resins, epoxy resins, and melamine resins), particles, initiators (thermal polymerization initiators, photopolymerization initiators), leveling agents, and fillers (e.g., synthetic smectite).
[0041] Examples of the particles include inorganic particles and organic particles. Examples of the inorganic particles include inorganic oxide particles. Examples of the materials of the inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of the materials of the organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.
[0042] The content ratio of inorganic particles is preferably low. The lower the content ratio of inorganic particles, the more the scattering of light caused by inorganic particles can be suppressed, and the manufacturing cost can be reduced. The content ratio of inorganic particles in the hard coat composition is, for example, 20 mass% or less, preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 1 mass% or less, particularly preferably 0.5 mass% or less, most preferably 0.2 mass% or less, even 0.1 mass% or less, and even 0.0 mass% from the viewpoint of visibility (described later).
[0043] The hardcoat composition can be diluted, if necessary, with a solvent, such as, for example, butyl acetate, ethyl acetate, toluene, and cyclopentanone.
[0044] When the hard coat composition is diluted with a solvent, the solids concentration is, for example, 10 mass % or more, preferably 30 mass % or more, and for example, 70 mass % or less, preferably 60 mass % or less.
[0045] As will be described in detail later, the hard coat layer is formed by applying a hard coat composition to one surface in the thickness direction of the base layer 3, and drying and curing it as necessary.
[0046] The hard coat layer preferably has transparency. Specifically, the total light transmittance (JIS K 7375-2008) of the hard coat layer is, for example, 80% or more, preferably 85% or more.
[0047] The thickness of the cured resin layer 4 is, for example, 0.5 μm or more, preferably 2 μm or more, more preferably 3 μm or more, and for example, 30 μm or less, preferably 25 μm or less, more preferably 20 μm or less.
[0048] <Arithmetic mean roughness Sa, minimum autocorrelation length Sal and development area Sdr> The arithmetic mean roughness Sa of one surface in the thickness direction of the cured resin layer 4 is 0.80 nm or more, preferably 1.00 nm or more, more preferably 1.00 nm or more, and is 4.50 nm or less, preferably 3.50 nm or less, more preferably 3.00 nm or less, and even more preferably 2.50 nm or less.
[0049] If the arithmetic mean roughness Sa is equal to or greater than the above lower limit, the adhesion can be improved due to the anchor effect.
[0050] On the other hand, if the arithmetic mean roughness Sa is less than the lower limit, the unevenness of the cured resin layer 4 becomes too small, and the anchor effect cannot be sufficiently exhibited, resulting in a decrease in adhesion.
[0051] Furthermore, if the arithmetic mean roughness Sa is equal to or less than the above upper limit, the adhesion can be improved due to the anchor effect.
[0052] On the other hand, if the arithmetic mean roughness Sa exceeds the upper limit, the unevenness of the cured resin layer 4 becomes excessively high, the strength decreases, and the anchor effect cannot be sufficiently exhibited, resulting in a decrease in adhesion.
[0053] The arithmetic mean roughness Sa can be calculated based on ISO 25178 by observing one surface in the thickness direction of the cured resin layer 4 with an atomic force microscope.
[0054] The minimum autocorrelation length Sal of one surface in the thickness direction of the cured resin layer 4 is 40 nm or less, preferably 30 nm or less, more preferably 20 nm or less, and for example, 1 nm or more, preferably 5 nm or more, more preferably 10 nm or more.
[0055] If the minimum autocorrelation length Sal is equal to or less than the above upper limit, the visibility can be improved.
[0056] On the other hand, if the minimum autocorrelation length Sal exceeds the upper limit, then irregularities having a long period are formed, which tend to cause light to be diffused or scattered, thereby reducing visibility.
[0057] The minimum autocorrelation length Sal is the shortest distance in the lateral direction at which the autocorrelation function decays to 0.2. The minimum autocorrelation length Sal can be calculated based on ISO 25178 by observing one surface in the thickness direction of the cured resin layer 4 with an atomic force microscope.
[0058] The developed area Sdr is 1.0% or more, preferably 3.0% or more, more preferably 5.0% or more, and is 30% or less, preferably 20% or less, more preferably 10% or less.
[0059] If the developed area Sdr is equal to or greater than the lower limit, the adhesion can be improved due to the anchor effect.
[0060] On the other hand, if the development area Sdr is less than the lower limit, the contact area between the cured resin layer 4 and the inorganic layer 11 cannot be sufficiently secured in the adhesion between the cured resin layer 4 and the inorganic layer 11. As a result, the adhesion is reduced.
[0061] If the developed area Sdr is equal to or less than the upper limit, the adhesion can be improved due to the anchor effect.
[0062] On the other hand, if the developed area Sdr exceeds the upper limit, the interface unevenness becomes excessively large, and the adhesion decreases.
[0063] The developed area Sdr can be calculated based on ISO 25178 by observing one surface in the thickness direction of the cured resin layer 4 with an atomic force microscope.
[0064] In the film 1, by setting the arithmetic mean roughness Sa, the minimum autocorrelation length Sal, and the developed area Sdr within the above-mentioned predetermined ranges, it is possible to improve the adhesion and visibility.
[0065] To set the arithmetic mean roughness Sa, the minimum autocorrelation length Sal, and the developed area Sdr within the above-mentioned predetermined ranges, the surface of the cured resin layer 4 is subjected to an oxygen-LAICP treatment (described later). In the oxygen-LAICP treatment, for example, the conveying speed (described later), the type of LA21 (described later), the oxygen concentration in the vacuum chamber during the oxygen-LAICP treatment (described later), the pressure in the vacuum chamber during the oxygen-LAICP treatment (described later), the frequency and magnitude of the high frequency power applied to the LA21 during the oxygen-LAICP treatment (described later), and the plasma current density during the oxygen-LAICP treatment (described later) are adjusted.
[0066] <Carbon element ratio C 90 , oxygen element ratio O 90 , carbon element ratio C 15 and oxygen element ratio O 15 > The film 1 preferably has a carbon element ratio C measured by the following test. 90 , oxygen element ratio O 90 , carbon element ratio C 15 and oxygen element ratio O 15 satisfies the following formula (1). O 15 / C 15 >O 90 / C 90 (1)
[0067] The test was carried out by: (1) measuring the carbon element ratio C 90 and oxygen element ratio O 90 Then, (2) X-ray photoelectron spectroscopy was used to adjust the photoelectron take-off angle to 15° with respect to one surface in the thickness direction of the cured resin layer 4, and the carbon element ratio C 15 and oxygen element ratio O 15 This is a test that measures:
[0068] Carbon element ratio C measured by the above test 90 , oxygen element ratio O 90 , carbon element ratio C 15 and oxygen element ratio O 15 However, if the above formula (1) is satisfied, the adhesion can be improved.
[0069] Specifically, in X-ray photoelectron spectroscopy, the smaller the photoelectron take-off angle, the shallower the detection depth relative to the surface of the film 1 (specifically, the cured resin layer 4), whereas the larger the photoelectron take-off angle, the deeper the detection depth relative to the surface of the film 1 (cured resin layer 4).
[0070] In other words, the carbon element ratio C 15 is the carbon element ratio based on a relatively shallow detection depth, and the carbon element ratio C 90 is the carbon element ratio based on a relatively deep detection depth.
[0071] In other words, the carbon element ratio C 15 is the carbon element ratio derived from the surface vicinity of the film 1 (cured resin layer 4), and the carbon element ratio C 90 is the carbon element ratio originating from the inside of the film 1 (cured resin layer 4).
[0072] Similarly, the oxygen element ratio O 15 is the oxygen element ratio derived from the surface vicinity of the film 1 (cured resin layer 4), and the oxygen element ratio O 90 is the oxygen element ratio originating from the inside of the film 1 (cured resin layer 4).
[0073] Satisfying the above formula (1) means that the oxygen element ratio is higher near the surface of the film 1 (cured resin layer 4) than inside the film 1 (cured resin layer 4).
[0074] From this, it is presumed that the surface of the film 1 (cured resin layer 4) is modified with oxygen, which causes chemical bonding between the film 1 (cured resin layer 4) and the inorganic layer 11 (described later) via oxygen, improving adhesion.
[0075] To satisfy the above formula (1), the surface of the cured resin layer 4 is subjected to oxygen-LAICP treatment (described later). In the oxygen-LAICP treatment, for example, the conveying speed (described later), the type of LA21 (described later), the oxygen concentration in the vacuum chamber during the oxygen-LAICP treatment (described later), the pressure in the vacuum chamber during the oxygen-LAICP treatment (described later), the frequency and magnitude of the high frequency power applied to the LA21 during the oxygen-LAICP treatment (described later), and the plasma current density during the oxygen-LAICP treatment (described later) are adjusted.
[0076] <Film manufacturing method> The method for producing the film includes a first step of preparing a base layer 3, a second step of disposing a cured resin layer 4 on one surface in the thickness direction of the base layer 3, and a third step of performing a plasma treatment on one surface in the thickness direction of the cured resin layer 4. This method is preferably carried out by a roll-to-roll method. In such a case, the conveying speed is, for example, 0.1 m / min or more, and, for example, 20.0 m / min or less, preferably 10.0 m / min or less, more preferably 5.0 m / min or less, and even more preferably 2.0 m / min or less. In the following description, the case where the cured resin layer 4 is a hard coat layer will be described in detail.
[0077] [1st step] In the first step, the base layer 3 is prepared.
[0078] [Second process] In the second step, a hard coat layer (cured resin layer 4) is disposed on one surface in the thickness direction of the substrate layer 3. To dispose a hard coat layer on one surface in the thickness direction of the substrate layer 3, a hard coat composition is applied to one surface in the thickness direction of the substrate layer 3, and then dried and cured as necessary to form the hard coat layer.
[0079] As for the drying conditions, the drying temperature is, for example, 50° C. or more and, for example, 120° C. or less. The drying time is, for example, 10 seconds or more and, for example, 10 minutes or less.
[0080] When the hard coat composition contains an ultraviolet-curable resin, the curable resin is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The cumulative irradiation amount of ultraviolet light is, for example, 100 mJ / cm. 2 or more, for example, 500 mJ / cm 2 The following is the result.
[0081] When the hard coat composition contains a thermosetting resin, the thermosetting resin is cured by heating. The heating temperature is, for example, 100° C. or more and, for example, 150° C. or less. The heating time is, for example, 10 seconds or more and, for example, 10 minutes or less.
[0082] In this way, the hard coat layer (cured resin layer 4) is disposed on one surface in the thickness direction of the base layer 3, and an intermediate laminate 2 including the base layer 3 and the hard coat layer (cured resin layer 4) in this order is produced.
[0083] [3rd step] In the second step, one surface in the thickness direction of the hard coat layer (cured resin layer 4) is subjected to a plasma treatment.
[0084] Specifically, the plasma treatment includes a treatment using inductively coupled plasma of an oxygen-containing gas (oxygen-LAICP treatment) generated by applying high-frequency power to a low-inductance antenna.
[0085] The low inductance antenna means an antenna that has a low inductance of 7.5 μH or less and is capable of generating inductively coupled plasma by application of high frequency power.
[0086] 2 and 3, the low inductance antenna 21 (LA21) is supported by a mounting fixture 22 and arranged in a state of being covered by a cover block 23 (omitted in FIG. 3) (a case where the number of LA21 is four is illustrated as an example). The multiple LA21 are arranged in an array so as to be aligned in the running direction of the intermediate laminate 2 and in a direction perpendicular to the running direction (the width direction of the intermediate laminate 2).
[0087] The LA21 is formed of a conductor. Examples of the conductor include copper and silver, and preferably copper. The LA21 may be covered with an insulator. Examples of the insulator include glass and quartz.
[0088] The LA 21 is electrically connected to a high-frequency power source (RF power source) via an impedance matching box.
[0089] The LA21 has an open loop shape. The open loop shape of the LA21 can reduce the inductance of the LA21. Therefore, the open loop shape of the LA21 can suppress an increase in voltage caused by an increase in power applied to the LA21. This can suppress abnormal discharge during plasma processing. Suppressing abnormal discharge can suppress damage to the intermediate laminate 2 being plasma processed.
[0090] Specifically, the LA 21 has a U-shape with two free ends. For each LA 21, the two free ends are fixed to the fixture 22 so as to be aligned in the width direction of the intermediate laminate 2. More specifically, the LA 21 is fixed to the fixture 22 via a feedthrough 24 as shown in FIG.
[0091] Moreover, the LA 21 has an extension portion 21a on the side opposite to the two free ends. The extension portion 21a extends in the width direction of the intermediate laminate 2. Each extension portion 21a may extend in the running direction of the intermediate laminate 2 (two LAs 21 may be arranged in this manner).
[0092] The LA21 extends from the fixture 22 toward the intermediate laminate 2. The LA21 extends in a direction perpendicular to the fixture 22. The extension length d1 of the LA21 from the fixture 22 is, for example, 30 mm or more and, for example, 150 mm or less.
[0093] The maximum length d2 of the LA21 in the planar direction of the intermediate laminate 2 is, for example, 50 mm or more and, for example, 150 mm or less.
[0094] The separation distance d3 between the LA 21 and the intermediate laminate 2 is, for example, 50 mm or more, and, for example, 200 mm or less.
[0095] Preferably, the extension length d1 and the separation distance d3 are the same.
[0096] The ratio (d3 / d1) of the separation distance d3 to the extension length d1 is, for example, not less than 0.5 and not more than 3.5.
[0097] The center-to-center distance d4 between adjacent LAs 21 in the running direction of the intermediate laminate 2 is, for example, 100 mm or more, and, for example, 500 mm or less. The number (number of rows) of LAs 21 spaced apart in the running direction of the intermediate laminate 2 may be 1, 2 or 3 depending on the running speed of the intermediate laminate 2 (i.e., plasma treatment time), or may be 4 or more if necessary.
[0098] The center-to-center distance d5 between adjacent LAs 21 in the width direction of the intermediate stack 2 is, for example, 200 mm or less, or, for example, 500 mm or less. The uniformity of the plasma density in the width direction of the intermediate stack 2 can be controlled.
[0099] Preferably, the center distance d4 and the center distance d5 are the same.
[0100] The centers of the extensions 21a of the four LAs 21 preferably form a square with the vertices as vertices. Such a set of LAs 21 can generate high density plasma with high in-plane uniformity. For example, the high frequency antenna for plasma generation described in JP 2013-258153 A can be used as the LA 21.
[0101] Also, the LA21 may have a coil shape instead of an open loop shape.
[0102] The cover block 23 includes a block body 23A and a plurality of partition plates 23B. The block body 23A has a plurality of storage spaces 23a. Each storage space 23a stores one LA 21. The partition plates 23B are arranged to close the storage space 23a. The storage space 23a is an enclosed space. In the cover block 23, the block body 23A is made of, for example, aluminum. An example of the aluminum is aluminum A5052. The partition plates 23B are made of an insulating material. An example of the insulating material is quartz and glass. The separation distance d' (shown in FIG. 3) between the traveling intermediate stack 2 and the cover block 23 is, for example, 50 mm or more, and, for example, 200 mm or less. Such a cover block 23 helps to avoid damage and contamination of the LA21 due to plasma processing without excessively reducing the plasma conversion efficiency due to the power applied to the LA21, and also helps to suppress damage to the intermediate laminate 2 being plasma processed.
[0103] In the oxygen-LAICP process, the LA 21 is placed in a vacuum chamber, and the intermediate laminate 2 is transported thereinto, and oxygen is supplied into the vacuum chamber.
[0104] From the viewpoint of improving adhesion, the oxygen concentration in the vacuum chamber is, for example, 30 vol.% or more, more preferably 50 vol.% or more, and even more preferably 80 vol.% or more, and from the viewpoint of improving adhesion, it is, for example, 100 vol.% or less, preferably 95 vol.% or less, and more preferably 90 vol.% or less.
[0105] In addition, an inert gas or an active gas other than oxygen may be introduced into the vacuum chamber. Examples of the inert gas include rare gases (argon, krypton, and xenon). Examples of the active gas include nitrogen and water vapor.
[0106] The pressure in the vacuum chamber during the oxygen-LAICP treatment is, for example, 0.1 Pa or more, preferably 0.2 Pa or more, more preferably 0.3 Pa or more, and for example, 7.0 Pa or less, preferably 5.0 Pa or less, more preferably 3.0 Pa or less, and further preferably 1.0 Pa or less. The pressure can be adjusted by the amount of oxygen supplied to the vacuum chamber.
[0107] In addition, the frequency of the high-frequency power applied to LA21 during oxygen-LAICP treatment is, for example, 1 MHz or more, preferably 3 MHz or more, more preferably 5 MHz or more, even more preferably 10 MHz or more, and for example, 100 MHz or less, preferably 80 MHz or less, more preferably 60 MHz or less.
[0108] The high frequency power is, for example, 2.5 kW or more, preferably 3.0 kW or more, more preferably 4.0 kW or more, and for example, 10 kW or less, preferably 8 kW or less, more preferably 6 kW or less.
[0109] In the oxygen-LAICP process, the plasma current density at the intermediate position between the LA 21 and the intermediate laminate 2 is, for example, 1.0 mA / cm 3 More than 2.0 mA / cm 3 More preferably, 3.0 mA / cm 3More preferably, 4.0 mA / cm 3 or more, for example, 10 mA / cm 3 Less than or equal to 8mA / cm 3 Less than or equal to 5 mA / cm, more preferably 3 The following is the result.
[0110] The plasma current density can be adjusted by the amount of oxygen introduced, the frequency of the high frequency power, and the high frequency power.
[0111] In this way, one surface in the thickness direction of the hard coat layer (cured resin layer 4) is subjected to plasma treatment, and the film 1 is produced.
[0112] <Laminate> As shown in FIG. 4, laminate 10 comprises film 1 (specifically, film 1 of the above-mentioned first embodiment or film 1 of the above-mentioned second embodiment) and inorganic layer 11, in that order toward one side in the thickness direction (note that FIG. 4 shows the case where film 1 is film 1 of the above-mentioned second embodiment). Specifically, laminate 10 comprises film 1 and inorganic layer 11 disposed directly on the upper surface (one side in the thickness direction) of film 1. Laminate 10 preferably comprises film 1 and inorganic layer 11.
[0113] [film] The film 1 is disposed over the entire lower surface of the inorganic layer 11 so as to be in contact with the lower surface of the inorganic layer 11. The film 1 is the lowermost layer in the laminate .
[0114] [Inorganic layer] The inorganic layer 11 has a film shape. The inorganic layer 11 is disposed on the entire upper surface of the film 1 so as to be in contact with the upper surface of the film 1. The inorganic layer 11 is the uppermost layer in the laminate 10.
[0115] Examples of the inorganic layer 11 include an anti-reflection layer and a conductive layer. Hereinafter, the cases where the inorganic layer 11 is an anti-reflection layer and a conductive layer will be described in detail.
[0116] (When the inorganic layer is an anti-reflection layer) With reference to FIG. 5, the case where the inorganic layer 11 is an anti-reflection layer will be described in detail.
[0117] When the inorganic layer 11 is an anti-reflection layer, the laminate 10 is an anti-reflection film.
[0118] The antireflection layer includes a plurality of layers having different refractive indices along the thickness direction. Specifically, the antireflection layer includes high refractive index layers having a relatively high refractive index and low refractive index layers having a relatively low refractive index alternately in the thickness direction. In the antireflection layer, the net reflected light intensity is attenuated by the interference between reflected light at a plurality of interfaces in the plurality of thin layers (high refractive index layers, low refractive index layers) included therein. In addition, in the antireflection layer, the interference effect of attenuating the reflected light intensity can be exerted by adjusting the optical film thickness (product of refractive index and thickness) of each thin layer. Such an antireflection layer includes high refractive index layers 12 and low refractive index layers 13 alternately in order toward one side in the thickness direction.
[0119] The antireflection layers (specifically, the high refractive index layer 12 and the low refractive index layer 13) preferably contain one selected from the group consisting of metals, alloys, metal oxides, metal nitrides, and metal fluorides, and more preferably contain one selected from the group consisting of metals, metal oxides, and metal nitrides, so that the antireflection layers can suppress the reflection intensity of external light.
[0120] Examples of metals include silicon, nickel, chromium, aluminum, tin, gold, silver, platinum, zinc, titanium, tungsten, zirconium, niobium, and palladium. Examples of alloys include alloys of the above metals. Examples of metal oxides include metal oxides of the above metals. Examples of metal nitrides include metal nitrides of the above metals. Examples of metal fluorides include metal nitrides of metal fluorides of the above metals.
[0121] In particular, the material used for the anti-reflective layer is selected depending on the desired refractive index.
[0122] Specifically, examples of the high refractive index material constituting the high refractive index layer 12 include niobium oxide (Nb2O5), titanium oxide, zirconium oxide, indium tin oxide (ITO), and antimony-doped tin oxide (ATO). As the high refractive index material, indium tin oxide (ITO) is preferable.
[0123] Examples of the low refractive index material constituting the low refractive index layer 13 include silicon dioxide (SiO2) and magnesium fluoride. As the low refractive index material, silicon dioxide (SiO2) is preferably used.
[0124] In the antireflection layer, the high refractive index layer 12 has a thickness of, for example, 1 nm or more, preferably 3 nm or more, and for example, 15 nm or less, preferably 10 nm or less.
[0125] Moreover, the thickness of the low refractive index layer 13 is thicker than the thickness of the high refractive index layer 12, and is, for example, more than 15 nm and, for example, 50 nm or less, preferably 30 nm or less.
[0126] The ratio of the thickness of the low refractive index layer 13 to the thickness of the high refractive index layer 12 (thickness of the low refractive index layer 13 / thickness of the high refractive index layer 12) is, for example, more than 1, preferably 2 or more, more preferably 3 or more, and for example, 10 or less, preferably 5 or less.
[0127] The thickness of the antireflection layer is, for example, 20 nm or more, and, for example, 300 nm or less, preferably 250 nm or less, and more preferably 200 nm or less.
[0128] When the inorganic layer 11 is an anti-reflective layer, the laminate 10 can be produced by disposing the anti-reflective layer on one surface of the film 1 in the thickness direction by a known sputtering method.
[0129] In the antireflection layer, the number of high refractive index layers and low refractive index layers is not particularly limited.
[0130] (When the inorganic layer is a conductive layer) When the inorganic layer 11 is a conductive layer, the laminate 10 is a transparent conductive film.
[0131] Examples of materials for the conductive layer include metals and metal oxides. Examples of metals include copper, silver, gold, nickel, chromium, and alloys thereof. Examples of metal oxides include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of indium-containing conductive oxides include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of antimony-containing conductive oxides include antimony tin composite oxide (ATO).
[0132] The conductive layer has a thickness of, for example, 1 nm or more, preferably 5 nm or more, and for example, 100 nm or less.
[0133] When the inorganic layer 11 is a conductive layer, the laminate 10 can be produced by disposing a conductive layer on one surface of the film 1 in the thickness direction by a known sputtering method.
[0134] <Action and effect> In the film 1, the arithmetic mean roughness Sa of one surface in the thickness direction of the cured resin layer 4 is within a predetermined range. Therefore, it is possible to form projections and recesses on one surface in the thickness direction of the cured resin layer 4 to a degree that can fully exert the anchor effect. As a result, it is possible to improve the adhesion.
[0135] In addition, the development area Sdr is within a predetermined range. Therefore, in the adhesion between the cured resin layer 4 and the inorganic layer 11, a sufficient contact area between the cured resin layer 4 and the inorganic layer 11 can be ensured. As a result, the adhesion can be improved.
[0136] Furthermore, the minimum autocorrelation length Sal of one surface in the thickness direction of the cured resin layer 4 is equal to or less than a predetermined value. Therefore, it is possible to form irregularities having a short period on one surface in the thickness direction of the cured resin layer 4. Such irregularities can prevent the light from diffusing or scattering, which would otherwise cause a decrease in visibility. As a result, it is possible to improve visibility.
[0137] The laminate 10 includes the film 1 and the inorganic layer 11 in this order toward one side in the thickness direction. Therefore, there is excellent adhesion between the film 1 and the inorganic layer 11. Also, visibility can be improved. EXAMPLES
[0138] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit values (numerical values defined as "less than or equal to" or "less than") or lower limit values (numerical values defined as "more than or equal to" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".
[0139] Example 1 <Film manufacturing> [1st step] In the first step, a base layer was prepared. Specifically, a long TAC film (triacetyl cellulose film, length 100 m, width 340 mm, thickness 40 μm) was first prepared as the base layer.
[0140] [Second process] In the second step, a hard coat layer (cured resin layer) was disposed on one surface in the thickness direction of the substrate layer. Specifically, first, 100 parts by mass (solid content equivalent value) of a butyl acetate solution of ultraviolet-curable acrylic urethane resin (product name "Luxidia 17-806", solid content concentration 80% by mass, manufactured by DIC Corporation), 5 parts by mass of a photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins), 0.03 parts by mass of a leveling agent (product name "GRANDIC PC4100", manufactured by DIC Corporation), and butyl acetate as a solvent were mixed to adjust the solid content concentration to 75% by mass, and then cyclopentanone was added as a solvent to prepare a hard coat composition (solid content concentration 50% by mass).
[0141] Next, a hard coat composition was applied to one surface of the substrate layer in the thickness direction to form a coating film. Next, the coating film was dried by heating and then cured by UV irradiation. As a result, a hard coat layer (thickness 5 μm) was disposed on one surface of the substrate layer in the thickness direction.
[0142] The heating temperature was 100° C., and the heating time was 60 seconds. For ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet rays with a wavelength of 365 nm were irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm 2 . 2 It was decided.
[0143] In this manner, an intermediate laminate having the base layer and the hard coat layer (cured resin layer) in that order was produced.
[0144] [3rd step] In the third step, one surface in the thickness direction of the hard coat layer was subjected to a plasma treatment.
[0145] Specifically, the intermediate laminate was transported into a vacuum chamber by a roll-to-roll method (transport speed: 1.0 m / min) under vacuum, and the intermediate laminate was subjected to a plasma treatment.
[0146] The plasma treatment was performed using oxygen-LAICP. The low-inductance antenna shown in Figures 2 and 3 was used.
[0147] In the low inductance antenna, the extension length d1 is 88 mm, the maximum length d2 is 100 mm, the separation distance d3 is 112 mm, the center distance d4 is 290 mm, the center distance d5 is 280 mm, and the separation distance d' is 100 mm. Each low inductance antenna is electrically connected to a high frequency power source (RF power source, frequency 13.56 MHz) via an impedance matching device.
[0148] The ultimate vacuum of the vacuum chamber is 1.0×10 -4 After evacuating the inside of the device until the pressure reached 0.5 Pa, oxygen gas (oxygen concentration 100% by volume) was introduced as an inert gas into the vacuum chamber, and the pressure inside the vacuum chamber was set to 0.5 Pa. By applying high frequency power of 5.0 kW to the four low inductance antennas by a high frequency power source, an inductively coupled plasma of an oxygen-containing gas was formed around the antennas (the hard coat layer was treated with this plasma). The plasma current density at the midpoint between the low inductance antennas and the intermediate laminate was set to 4.2 mA / cm. 3 It was decided.
[0149] In this way, a film was produced.
[0150] <Manufacture of Laminate> An antireflection layer was formed by sputtering on one surface of the film in the thickness direction.
[0151] Specifically, after evacuating the vacuum chamber, -4The pressure was reduced to 100 Pa, argon gas was introduced as a sputtering gas, and a high refractive index layer (ITO film, thickness 5 nm) was placed on an ITO target (SnO ratio 10 mass%, length 600 mm x width 150 mm x thickness 5 mm, single cathode system) (input power 1.0 kW, deposition chamber pressure: 0.3 Pa, DC discharge). Next, a low refractive index layer (SiO2 film, thickness 20 nm) was placed on a pure Si target (length 600 mm x width 50 mm x thickness 5 mm, dual cathode system) (input power: 3.0 kW, deposition pressure 0.3 Pa, O2 / Ar=0.3, MFAC power supply 60 kHz).
[0152] In this way, a laminate was produced.
[0153] Example 2 A film and a laminate were produced according to the same procedure as in Example 1. However, in the third step, the conveying speed was changed to 0.5 m / min.
[0154] Comparative Example 1 A film and a laminate were produced according to the same procedure as in Example 1, except that the third step was not carried out.
[0155] Comparative Example 2 A film and a laminate were produced according to the same procedure as in Example 1. However, in the third step, one surface in the thickness direction of the hard coat layer was subjected to a bombardment treatment with argon ions.
[0156] Specifically, the intermediate laminate was transported to a vacuum chamber in a roll-to-roll manner under vacuum.
[0157] The vacuum chamber is equipped with a pair of flat electrodes for generating plasma, a cathode electrode and an anode electrode (both rectangular electrodes made of SUS304). The pair of flat electrodes are arranged with a gap of 50 mm between them, parallel to the intermediate laminate passing through the vacuum chamber. The anode electrode is arranged so as to be in constant contact with the intermediate laminate passing through the vacuum chamber, and is grounded outside the vacuum chamber. The cathode electrode is arranged at a position 35 mm away from the intermediate laminate, and is electrically connected to a high-frequency power source (RF power source, 13.56 MHz) via an impedance matching device. The length of each electrode in the film running direction is 110 mm, and the length in the width direction is 430 mm.
[0158] The ultimate vacuum of the vacuum chamber is 1.0×10 -4 After evacuating the inside of the apparatus until the pressure reached 0.5 Pa, argon gas was introduced as an inert gas into the vacuum chamber, and the pressure in the vacuum chamber was set to 0.5 Pa. Capacitively coupled plasma (CCP) was generated by applying 700 W of power between the planar electrodes using a high-frequency power source. In this plasma environment, the surface of the intermediate laminate (hard coat layer) was bombarded with argon ions.
[0159] Comparative Example 3 A film and a laminate were produced based on the same procedure as in Example 1. However, in the third step, the power applied between the planar electrodes by the high-frequency power supply was changed to 2.0 kW.
[0160] Comparative Example 4 A film and a laminate were manufactured based on the same procedure as in Comparative Example 2. However, in the following procedure, in the second step, a hard coat layer (cured resin layer) was disposed on one surface in the thickness direction of the base layer. Specifically, first, a methyl ethyl ketone dispersion (Shin-Etsu Silicone's "QSG-30", solid content concentration: 30 mass%) of silica particles having a number-average primary particle diameter of 30 nm (refractive index at a wavelength of 405 nm: 1.47) was added to and mixed with an ultraviolet-curable acrylic resin composition (DIC's "GRANDIC PC-1070", refractive index at a wavelength of 405 nm: 1.55) to prepare a hard coat composition. The amount of silica particles added was adjusted so that the amount of silica particles relative to the total solid content (total of resin and particles) of the hard coat layer was 45 mass%.
[0161] Next, a hard coat composition was applied to one surface of the substrate layer in the thickness direction to form a coating film. Next, the coating film was dried by heating and then cured by UV irradiation. As a result, a hard coat layer (thickness 5 μm) was disposed on one surface of the substrate layer in the thickness direction.
[0162] The heating temperature was 100° C., and the heating time was 60 seconds. For ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet rays with a wavelength of 365 nm were irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm 2 . 2 It was decided.
[0163] <Evaluation> [arithmetic surface height Sa, minimum autocorrelation length Sal, and development area Sdr] The surface shape of one surface in the thickness direction of the cured resin layer (hard coat layer) in the film of each Example and Comparative Example was observed using an atomic force microscope under the following conditions, and the arithmetic surface height Sa, minimum autocorrelation length Sal, and developed area Sdr were calculated. The results are shown in Table 1. The surface shapes are also shown in Figs. 6 to 11. Specifically, Fig. 6 shows the surface shape of Example 1, Fig. 7 shows the surface shape of Example 2, Fig. 8 shows the surface shape of Comparative Example 1, Fig. 9 shows the surface shape of Comparative Example 2, Fig. 10 shows the surface shape of Comparative Example 3, and Fig. 11 shows the surface shape of Comparative Example 4. {conditions} Equipment: Bruker Dimension Edge Measurement mode: Tapping mode Cantilever: Si single crystal Measurement field of view: 1μm×1μm
[0164] [Carbon element ratio C 90 , oxygen element ratio O 90 , carbon element ratio C 15 and oxygen element ratio O 15 Measurement of The films of the examples and comparative examples were subjected to the following tests.
[0165] The film was cut out from the center in the width direction (340 mm width) to a size of about 1 cm square and used as a sample.
[0166] Specifically, in the test, (1) X-ray photoelectron spectroscopy was used to measure the carbon element ratio C 90 and oxygen element ratio O 90 Next, (2) the carbon element ratio C was measured by X-ray photoelectron spectroscopy with the photoelectron take-off angle adjusted to 15° with respect to one surface in the thickness direction of the hard coat layer. 15 and oxygen element ratio O 15 was measured.
[0167] The conditions for X-ray photoelectron spectroscopy are as follows. {conditions} Equipment: "KRATOS ULTRA2" (Shimadzu Corporation) X-ray source: Monochrome Al Kα X-ray setting:700×300μm [5mA, 75W] Static neutralization: yes
[0168] Table 1 shows whether the above formula (1) is satisfied.
[0169] [Adhesion] The laminates of each Example and Comparative Example were cut into a size of 50 mm x 50 mm to prepare samples. Next, cuts were made at 1 mm intervals on the treated surface of the sample to create a grid of 100 squares, and then the sample was placed in a weather resistance tester under the following conditions. {conditions} SUV irradiation conditions Temperature and humidity conditions: 85℃45%Rh Light source used: Metal halide lamp Irradiation conditions: 150mW / cm 2 (290-450nm)
[0170] Next, 2 mL of isopropyl alcohol was continuously dropped onto the surface of the anti-reflective layer to prevent it from drying out, and a polyester wiper (Anticon Gold, manufactured by Sanplatec) fixed to a 20 mm square SUS jig was rubbed over the grid (load: 1.5 kg, 1000 strokes). A grid in which the anti-reflective layer had peeled off over an area of 1 / 4 or more of the grid area was counted as "peeling." The adhesion was evaluated based on the following criteria. The results are shown in Table 1. {standard} ○: Peeling was 5 squares or less. ×: The peeling exceeded 5 squares.
[0171] [Visibility] For the films of each Example and Comparative Example, a black acrylic plate (manufactured by Mitsubishi Chemical) having a thickness of 2 mm was attached to the other surface in the thickness direction of the base layer via a transparent acrylic adhesive. Next, light from a white LED was irradiated from a direction of 45° to the normal line of the other surface in the thickness direction of the base layer. Next, the reflected light was visually observed from a direction of 70 to 80° to the normal line of the other surface in the thickness direction of the base layer, and the visibility was evaluated according to the following criteria. The results are shown in Table 1. {standard} ◯: The reflected light was colorless. ×: Reflected light was perceived as white or pale blue. The white or bluish-white appearance is due to the phenomenon in which short wavelength light, in particular, is diffused or scattered by surface irregularities (external scattering) or particles contained in the cured resin layer (internal scattering).
[0172] [Table 1] [Explanation of symbols]
[0173] 1. Film 3 Base material layer 4 Cured resin layer 10 Laminate 11 Inorganic layer
Claims
1. A base material layer and a cured resin layer are provided in this order toward one side in a thickness direction, The arithmetic average roughness Sa of one surface in the thickness direction of the cured resin layer is 0.80 nm or more and 4.50 nm or less, The minimum autocorrelation length Sal of one surface in the thickness direction of the cured resin layer is 40 nm or less, A film, wherein a developed area Sdr of one surface in a thickness direction of the cured resin layer is 1.0% or more and 30% or less.
2. Carbon element ratio C measured by the following test 90 , oxygen element ratio O 90 , carbon element ratio C 15 and oxygen element ratio O 15 The film according to claim 1 , which satisfies the following formula (1): O 15 / C 15 >O 90 / C 90 (1) Test: (1) Using X-ray photoelectron spectroscopy, the photoelectron take-off angle was adjusted to 90° with respect to one surface in the thickness direction of the cured resin layer, and the carbon element ratio C 90 and oxygen element ratio O 90 Measure. (2) Using X-ray photoelectron spectroscopy, the photoelectron take-off angle was adjusted to 15° with respect to one surface in the thickness direction of the cured resin layer, and the carbon element ratio C 15 and oxygen element ratio O 15 Measure.
3. A laminate comprising the film according to claim 1 or 2 and an inorganic layer in that order toward one side in a thickness direction.
4. the inorganic layer is an anti-reflection layer, The laminate according to claim 3 , wherein the antireflection layer comprises a plurality of layers having mutually different refractive indices along a thickness direction.
5. The laminate according to claim 3 , wherein the inorganic layer is a conductive layer.
Citation Information
Patent Citations
Plasma etching method
JP2007051218A
Hard coat film, and manufacturing method thereof
JP2020157693A
Laminate film
JP2021074915A
Transparent substrate with antireflection coating and image display device
JP2023105806A
Antireflection film and image display device
JP2023163654A